PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. WAHANA SAFETY INDONESIA - Rahayu, Krida Puji; Cantika, Sella (RJABM (Research Journal of Accounting and Business Management), 2022)
This study aims to determine the Leadership Style and Organizational Culture on employee performance at PT Wahana Safety Indonesia simultaneously. This research is an associative-research with a quantitative approach. The independent variables used in this research are leadership style (x1) and organizational culture (x2). While the dependent variable or the dependent variable used in this study is employee performance (y). Sampling used in this study using the saturated sample method which is the entire existing population, namely all employees of PT Wahana Safety Indonesia as many as 150 employees. Data collection was carried out in this study using a questionnaire/questionnaire. The data analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression test and hypothesis testing with the results obtained that the regression value is Y = 3.571a + 0.0511 + 0.5232. Hypothesis test for leadership style variable (X1) obtained t-count < t-table (1.305 <1.976) with a significance value > 0.05 (0.194 >0.05) leadership style variable (X1) partially has positive but has no significant effect on employee performance (Y) at PT Wahana Safety Indonesia (H0 is accepted and Ha is rejected). Hypothesis test of organizational culture variable (x2) obtained t-count > t-table (18.279 > 1.976) with a significance value <0.05 (0.000 <0.05) organizational culture variable (X2) partially has a positive and significant effect on performance employee (Y) (H0 is rejected and Ha is accepted). While the hypothesis test is obtained by f-count > f-table (192.039 > 3.06) with a significance value of <0.05 (0.000 <0.05) then the results of the f-test of the independent variables leadership style (X2) and organizational culture (X2) are Simultaneous positive and significant effect on the dependent variable, namely employee performance (Y) at PT Wahana Safety Indonesia. Meanwhile, with the value of determination, 72.3% was found to be influenced by leadership style (X1) and organizational culture (X2) where the remaining 27.7% was influenced by other factors.